Tinjauan Maá¹£laá¸¥ah terhadap Metode IstinbÄá¹ Fatwa Majelis Ulama Indonesia tentang Asuransi Jiwa - Sarpini Sarpini (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2019)
In the Qur'an and al-Hadith there are no provisions that explicitly regulate insurance. Therefore, this insurance includes the issue of ijtihadiyah, it means that to determine the law of insurance whether halal or haram, it requires the role of fiqh scholars through ijtihad. This study uses descriptive analysis in which the authors describe all data about life insurance in a systematic, careful and factual with deductive pattern to propose theories or general propositions about maslahah then analyzing data on the basis and substance of Indonesian Ulema Council (MUI) fatwa on life insurance to obtain specific conclusion. This study concludes that the background of the emergence of the MUI fatwa on life insurance is due to public question about life insurance, whether the legal status or its activity are in accordance with the Shari'ah. The legal basis used by MUI in establishing fatwa on life insurance is the Qur'an, al-hadith and fiqh muamalah. MUI fatwa used istinbat method to regulate the life insurance viewed from the concept of maslahah is called maslahah the mu'tabarah (acceptable).